Nutritional Quality, Voluntary Intake and Enteric Methane Emissions of Diets Based on Novel Cayman Grass and Its Associations With Two Leucaena Shrub Legumes - Gaviria-Uribe, Xiomara; Bolivar, Diana M.; Rosenstock, Todd S.; Molina-Botero, Isabel Cristina; Chirinda, Ngonidzashe; Barahona, Rolando; Arango, Jacobo (Frontiers in Veterinary Science, 2020)
Methane (CH4) emissions from enteric fermentation in cattle are an important source of greenhouse gases, accounting for about 40% of all agricultural emissions. Diet quality plays a fundamental role in determining the magnitude of CH4 emissions. Specifically, the inclusion of feeds with high digestibility and nutritional value have been reported to be a viable option for reducing CH4 emissions and, simultaneously, increase animal productivity. The present study aimed to evaluate the effect of the nutritional composition and voluntary intake of diets based on tropical forages upon CH4 emissions from zebu steers. Five treatments (diets) were evaluated: Cay1: Urochloa hybrid cv. Cayman (harvested after 65 days of regrowth: low quality); Cay2: cv. Cayman harvested after 45 days of regrowth; CayLl: cv. Cayman + Leucaena leucocephala; CayLd: cv. Cayman + Leucaena diversifolia; Hay: Dichantium aristatum hay as a comparator of common naturalized pasture. For each diet representing different levels of intensification (naturalized pasture, improved pasture, and silvopastoral systems), CH4 emissions were measured using the polytunnel technique with four zebu steers housed in individual chambers. The CH4 accumulated was monitored using an infrared multigas analyzer, and the voluntary forage intake of each animal was calculated. Dry matter intake (DMI, % of body weight) ranged between 0.77 and 2.94 among diets offered. Emissions of CH4 per kg of DMI were significantly higher (P <.0001) in Cay1 (60.4 g), compared to other treatments. Diets that included Leucaena forage legumes had generally higher crude protein contents and higher DMI. Cay1 and Hay which had low protein content and digestibility had a higher CH4 emission intensity (per unit live weight gain) compared to Cay2, CayLl and CayLd. Our results suggest that grass consumed after a regrowth period of 45 days results in lower CH4 emissions intensities compared to those observed following a regrowth period of 65 days. Diets with Leucaena inclusion showed advantages in nutrient intake that are reflected in greater live weight gains of cattle. Consequently, the intensity of the emissions generated in the legume-based systems were lower suggesting that they are a good option for achieving the emission reduction goals of sustainable tropical cattle production.